2022
DOI: 10.3390/metabo12121260
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolome Profiling of Indonesian Shallots and Japanese Long-Day/Short-Day Bulb Onions

Kanako Matsuse,
Mostafa Abdelrahman,
Nur Aeni Ariyanti
et al.

Abstract: In this study, targeted metabolome analysis was applied to identify the discriminative metabolites between Indonesian shallot landraces, Japanese long-day onion (LDO) varieties, and Japanese short-day onion (SDO) varieties. In total, 172 metabolite signal intensities were subjected to multivariate PLS-DA, VIP, and random forest modeling to gain further insight into genotype-specific metabolites. PLS-DA divides the examined genotypes into three different clusters, implying that shallot landraces exhibited a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…According to the previous study ( 17 ), the shallot crude extract contains a complex mixture of many plant metabolites, such as alkaloids, glycosides, phenolics, terpenoids, and flavonoids, that can have potential as antibiotics. In line with other research ( 27 , 28 ), these compounds were found in Allium species and were found to have strong antimicrobial properties against bacteria, fungi, and viruses that infect humans. Based on the test results, it can be concluded that phytochemical compounds may have antimicrobial effects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to the previous study ( 17 ), the shallot crude extract contains a complex mixture of many plant metabolites, such as alkaloids, glycosides, phenolics, terpenoids, and flavonoids, that can have potential as antibiotics. In line with other research ( 27 , 28 ), these compounds were found in Allium species and were found to have strong antimicrobial properties against bacteria, fungi, and viruses that infect humans. Based on the test results, it can be concluded that phytochemical compounds may have antimicrobial effects.…”
Section: Discussionsupporting
confidence: 89%
“…The research related to the composition of shallots is still being explored. This is due to differences in varieties, climate, geography, soil fertility, and cultivation practices, which play an important role in the proportion of compounds in shallots ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…PLS-DA, a well-known technique for feature extraction and discriminant analysis in chemometrics, is used to reveal important patterns related to physiological, genetic, and environmental issues. PLS-DA generates visual scatter plots for the qualitative evaluation of variability among multivariate data, and it is now widely used to assess differences among plant species at the metabolome level (Matsuse et al 2022;Zhao et al 2022a). The PLS-DA (R 2 X = 0.9998) was used to analyze the HPLC data.…”
Section: Chemical Analysis Of the Main Alkaloidsmentioning
confidence: 99%